High-temperature electrical properties of polymer-derived ceramic SiBCN thin films fabricated by direct writing. Issue 11 (1st June 2022) - Wu, Chao; Pan, Xiaochuan; Lin, Fan; Cui, Zaifu; Li, Xin; Chen, Guochun; Liu, Xianlong; He, Yingping; He, Gonghan; Hai, Zhenyin; Chen, Qinnan; Sun, Daoheng
Abstract: The in situ temperature monitoring of hot components in harsh environments remains a challenging task. In this study, SiBCN thin-film resistance grids with thicknesses of 1.8 μm were fabricated on alumina substrates via direct writing. Owing to their dense microscopic morphology and extremely high graphitisation level, the produced SiBCN films exhibited large high-temperature oxidation resistance and electrical conductivity. The resistance–temperature, stability, and repeatability characteristics of these films were examined in an aerobic environment at temperatures up to 800 °C. The obtained results revealed that the thermistor resistance decreased monotonously with increasing temperature from room temperature to 800 °C. The SiBCN film resistance variations observed during repeated temperature cycling in the regions of 505–620 °C and 610–720 °C were 0.09% and 1.7%, respectively. The high cyclability and stability of the SiBCN thin film thermistor suggested its potential applicability for the in situ temperature monitoring of hot components in harsh environments. Highlights: A SiBCN thin-film thermistor with a thickness of 1.8 μm based on polymer-derived ceramics is fabricated via direct writing. The produced SiBCN thin film exhibits large high-temperature oxidation resistance despite the high content of free carbon. The resistance–temperature relationship of the SiBCN thin film between room temperature and 800 °C is determined.